(untitled) (Rajarshi Janak University Research Journal, 2025)
This study examines the evolving landscape of digital transformation in Nepal, focusing on the opportunities it presents and the challenges it faces. As a developing country with diverse geography and socio-economic disparities, Nepal is experiencing rapid digital growth, driven by increased internet access, mobile penetration, and government initiatives like the Digital Nepal Framework. The research identifies key sectors such as education, healthcare, governance, and agriculture where digital technologies offer transformative potential. At the same time, it highlights significant barriers including inadequate infrastructure, digital illiteracy, policy gaps, and resistance to change. Through a mixed-methods approach combining quantitative survey and qualitative insights, the study captures public perception, assesses the current state of digital adoption, and evaluates the effectiveness of ongoing initiatives. The findings emphasize the need for strategic investment in infrastructure, comprehensive digital literacy programs, inclusive policies, and collaborative efforts among government, private sector, and civil society. The study concludes that while challenges persist, digital transformation offers Nepal a critical opportunity to achieve inclusive growth and sustainable development if approached with coordinated action and long-term vision.